Individual features of the physical development and the onset of biological maturity of morphological and functional structures of the body - Oleksandr Aghyppo; Valeriy Druz; Tatyana Dorofeeva; Yaroslavna Puhach; Nina Buren; Mariia Nechytailo; Yana Zhernovnikova (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to justify the observed features of physical development of the individual and the nature of the flow pattern of biological maturity of morphological and functional structures of the body other than the population norm of behavior trends of these processes. Materials and Methods: analysis of scientific literature on the research, the use of survey data contingent of children of preschool and primary school age, the use of attributive semantic spaces, method of similarity and dimensions, the method of analogy, the method of slowly varying amplitudes. Results: the nature of occurrence of the individual characteristics of the physical development and the onset of biological maturity of morphological and functional structures of the whole organism. Substantiates the nature of occurrence of the individual variation of these processes. Conclusions: the existing differences in the individual development of physical and somatotype shaping involve a violation of the synchronization of interdependent relations system. This reduces the potential viability and is expressed in the constitution somatotype features that can be used for preclinical diagnosis